INTERVENSI NONFARMAKOLOGI UNTUK PENINGKATAN PRODUKSI DAN EJEKSI ASI: A LITERATURE REVIEW - DESMAWATI, DESMAWATI; TRIANANDA, DINDA (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2022)
ABSTRACTThe coverage of exclusive breast milk nationally in some areas is still not fulfilled. The cause is a lack of milk production so that nonpharmacological intervention is needed in increasing production in breast milk. This paper aims to understand and assess the effectiveness of nonpharmacological intrusion in increasing production in breast milk. This research uses literature review research study methods. Search based on The Google Scholar, Sciencedirect and PubMed databases and taking into account the criteria for inclusion value in English in 2015-2021, accredited to Sinta and available in fulltext with special searches, namely in increasing ejection and production in breast milk. Searches get 5,518 articles based on keyword screening results and search focuses on getting 17 articles for analysis. Literature Review is used to provide increased production and ejection in breast milk, namely by herbal lactagogue consumption, massage therapy, acupressure therapy, lactapuncture therapy, music therapy, and warm compress therapy. Increased production and ejection of breast milk is indicated based on the effectiveness of nonpharmacological interventions Conclusion: nonpharmacological interventions are proven to provide an increase in the production and ejection of breast milk. The result is expected to be a refence for increased production in breast milk.ABSTRAKCakupan ASI eksklusif secara nasional di beberapa daerah masih belum tercukupi. Penyebabnya adalah kekurangan produksi ASI sehingga dibutuhkan intervensi nonfarmakologis dalam peningkatan produksi pada ASI. Penulisan ini memiliki tujuan dalam memahami serta menilai efektivitas intrusi nonfarmakologis dalam peningkatan produksi pada ASI. Penelitian ini menggunakan metode studi penelitian Literature Review. Penelusuran berdasarkan database Google Scholar, Sciencedirect serta PubMed dan memerhatikan kriteria nilai inklusi dalam bahasa inggris pada tahun 2015- 2021, diakreditasi pada Sinta dan tersedia dalam fulltext dengan pencarian khusus yaitu dalam peningkatan ejeksi serta produksi pada ASI. Penelusuran mendapatkan 5.518 artikel berdasarkan hasil screening kata kunci dan pencarian berfokus mendapatkan 17 artikel untuk dianalisis. Literature Review digunakan untuk memberi peningkatan produksi dan ejeksi pada ASI yaitu dengan konsumsi lactagogue secara herbal, terapi pijat, terapi akupresur, terapi lactapuncture, terapi musik, dan terapi kompres hangat. Peningkatan produksi dan ejeksi ASI ditunjukkan berdasarkan keefektifan intervensi nonfarmakologi Simpulan: intervensi nonfarmakologis terbukti dapat memberikan peningkatan pada produksi dan ejeksi ASI. Hasilnya diharap menjadi suatu refensi untuk peningkatan produksi pada ASI.de